Aging-friendly cities: Investigating the effects of street usage on the psychological satisfaction of older adults in megacities - Li, Jian; Gao, Xing; Qiu, Yue; Ling, Yantao (Frontiers in Psychology, 2022)
The psychological satisfaction of older adults is an important evaluation standard for the construction of elder-friendly cities. Meanwhile, as important space carriers carrying the travel activities and social participation of older adults, streets are also of great significance to improve psychological wellbeing. However, few studies pay attention to the street usage of aging population, especially in the context of megacities. Moreover, the previous literature rarely distinguishes the types of streets. Thus, employing a mixed approach, we investigate the relationships between street usage and psychological satisfaction for older adults. Based on the survey in Shanghai, we find that a clear role for different usage indicators in the determination of subjective psychological satisfaction of older adults. More specially, the street usage and psychological satisfaction for older adults are strongly correlated, especially for living streets. Psychological satisfaction for older adults in different types of streets is not always positively related to the positive perception of street usage. The psychological satisfaction of different streets depends on different factors. By focusing on the case of a megacity, our study emphasizes the differences between different types of streets, which will be conducive to the proposal of practical planning policies. In addition, employing mixed research methods not only explains how different street usage affects the psychological welfare of older adults on a macro scale, but also emphasizes the inner world of respondents.